Big Five Traits, Entrepreneurial Awareness, and Financial Socialization Impacting Vocational High School Entrepreneurial Intentions - Respati, Dwi Kismayanti; Widyastuti, Umi; Purwana, Dedi; Sumiati, Ati; Michael Musyaffi, Ayatulloh (International Journal of Business, Law, and Education, 2023)
Empowering communities and educated groups through entrepreneurial programs are positively impacting the national economy. Vocational students frequently have specialised and practical abilities that they have developed through practical training. These skills can be directly applicable to various aspects of entrepreneurship, including product development, production, technical support, and more. This study aims to prove that the big five personality traits, entrepreneurial awareness, self-efficacy, and family financial socialization have contributed to entrepreneurial intention of students. 200 data were obtained from Indonesian vocational high school students, and processed with SEM-PLS. The result proved that awareness, self-efficacy, and some indicator of the big five personality has a positive affect on entrepreneurial intention among students. While family financial socialization has no impact on it. This study is a reference for schools and policy maker to provide education on entrepreneurship for vocational students. Understanding how different types of awareness (opportunities, resources, skills) influence intention can guide the development of targeted curriculum and training methods